Mastering Descriptive Text: A Study of Seventh Graders at SMP Kristen Makale - Boropadang, Febriani; Allo, Markus Deli Girik (Universitas Cokroaminoto Palopo, 2023)
English is a crucial international la nguage, and mastering its four core skills speaking, writing, reading, and listening is essential for learners. This study focuses on the reading skill, specifically students’ mastery of descriptive texts, which play a vital role in vocabulary expansion and grammatical understanding. Conducted at SMP Kristen Makale, this quantitative research investigates the ability of seventh-grade students to identify the generic structure and language features of descriptive texts. Data were collected via a multiple-choice test administered to 30 students, assessing comprehension of text components and grammar, such as the simple present tense, adjectives, and linking verbs. Results reveal that only 10% of students achieved a very good mastery level, while the majority exhibited fair to poor understanding. The findings indicate significant challenges in grasping key linguistic elements, suggesting the need for more interactive and focused instructional strategies. This study underscores the importance of tailored teaching approaches to improve students’ descriptive text comprehension, contributing to their overall English language proficiency.